Heterologous prime-boost vaccination based on Polymorphic protein D protects against intravaginal Chlamydia trachomatis infection in mice - Russi, Romina Cecilia (2022)
The control of the worldwide spread of sexually transmitted Chlamydia trachomatis (Ct) infection urgently demands the development of a preventive vaccine. In this work, we designed a vaccine based on a fragment of polymorphic protein D (FPmpD) that proved to be immunogenic enough to generate a robust systemic and mucosal IgG humoral immune response in two strains of mice. We used a heterologous prime-boost strategy, including simultaneous systemic and mucosal administration routes. The high titers of anti-PmpD antibodies elicited by this immunization scheme did not affect murine fertility. We tested the vaccine in a mouse model of Ct intravaginal infection. Anti-PmpD antibodies displayed potent neutralizing activity in vitro and protective effects in uterine tissues in vivo. Notably, the humoral immune response of PmpD-vaccinated mice was faster and stronger than the primary immune response of non-vaccinated mice when exposed to Ct. FPmpD-based vaccine effectively reduced Ct shedding into cervicovaginal fluids, bacterial burden at the genitourinary tract, and overall infectivity. Hence, the FPmpD-based vaccine might constitute an efficient tool to protect against Ct intravaginal infection and decrease the infection spreading.